세계 잡초연구 동향 및 전망 - 이인용(In-Yong Lee); 박태선(Tea-Seon Park); 최정섭(Jung Sup Choi); 고영관(Young-Kwan Ko); 박기웅(Kee Woong Park); 서현아(Hyun-A Seo) (Weed & turfgrass science, 2016)
This paper provides the current status of weed science and prospects for the development of weed science based on the research trends presented at the 7th International Weed Science Conference in 2016. Approximately 520 researchers from 59 countries, including Korea, participated in the conference and presented 625 papers in nine research areas. Major research topics were herbicide resistance, weed ecology, weed management in agricultural and non-agricultural lands, herbicide spray technology, and non-chemical weed control. Studies on herbicide resistance presented more than 30% of all papers presented. Particularly, resistance to non-selective herbicides, such as glyphosate and glufosinate-ammonium, and non-target sites of resistance mechanisms were the main subjects of the herbicide resistance research area. Moreover, the conference focused on research concerning herbicide resistant weeds of staple crops of the world (corn, wheat, and rice). Arylex was introduced as a new compound which has a mode of herbicidal action similar to synthetic auxin. Three compounds being developed as HPPD inhibitors were studied for ways to reduce their toxicity and tested as mixed with safeners. Additionally, parasitic weeds, which are not native to Korea, are an expanding research subject in the world. Although 45 years have passed since the first report of herbicide resistance in 1970, herbicide resistance remains a serious problem in most intensive cropping systems of the world and will continue to be a major area of study in the future. 세계 잡초연구자들이 세계잡초학회에서 발표한 최근 연구동향을 파악하여 이를 토대로 향후 잡초연구 발전방향과 전망을 제시하고자 하였다. 제 7차 세계잡초학회는 우리나라를 포함한 59개국 520여명이 참석하였으며, 9개 분야 625편이 발표되었다. 주요 연구분야로는 제초제 저항성잡초, 잡초생태, 농경지 및 비농경지의 잡초관리, 제초제 살포기술, 비화학적 잡초방제 등이었다. 이중 제초제 저항성잡초 연구분야는 전체 30%를 점유하여 향후에도 이들 연구가 지속될 것으로 판단된다. 특히 설포닐우레아계 보다는 비선택성 제초제인 glyphosate, glufosinate-ammonium 저항성 잡초에 대한 발표가 많았다. 신규 제초제 개발은 synthetic auxin 작용기작의 제초제인 arylex, HPPD 저해제로 개발 중인 3가지 물질을 safener와의 합제 연구 등이 있었다. 그리고 세계 주곡작물인 옥수수, 밀, 벼 재배지에서 발생되는 제초제 저항성잡초에 대한 연구가 집중되었다. 특히 잡초의 non-target site에 대한 저항성 연구가 집중적이었다. 또한 우리나라에는 없는 기생잡초에 대한 연구 폭이 넓어지고 있으며, 예년에는 취급하지 않았던 비화학적 잡초방제 부문도 많았다. 향후에는 제초제 저항성 메카니즘 구명, 기생잡초 연구, 제초제 살포기술, 비화학적 잡초방제 등의 연구가 폭넓게 진행될 것으로 전망되었다.